Immediate effect of subliminal priming with positive reward stimuli on standing balance in healthy individuals: A randomized controlled trial. Issue 28 (July 2017) - Aoyama, Yasuhiro; Uchida, Hiroyuki; Sugi, Yasuyuki; Kawakami, Akinobu; Fujii, Miki; Kiso, Kanae; Kono, Ryota; Takebayashi, Takashi; Hirao, Kazuki
Abstract: Background: Information received subconsciously can influence exercise performance; however, it remains unclear whether subliminal or supraliminal reward is more effective in improving standing balance ability when priming stimuli are subconsciously delivered. The present study aimed to compare the effects of subliminal priming-plus-subliminal reward stimuli (experimental) with subliminal priming-plus-supraliminal reward stimuli (control) on standing balance ability. Methods: This was a single-blind (outcome assessor), parallel-group, randomized controlled trial involving healthy young adults recruited from a university in Japan. Assessments were conducted at baseline and immediately after intervention. The primary outcome was the functional reach test (FRT) measurement. The secondary outcome was one-leg standing time (OLST) with eyes closed. Of the 52 participants screened, 25 were randomly assigned to experimental and control groups each. Results: Both interventions were effective for improving the FRT between the baseline and intervention; however, smaller improvements were observed in the experimental group. We found a large between-groups effect size immediately after the intervention for the FRT ( d  = −0.92). In contrast, there were no differences in improvements in OLST between the 2 groups ( d  = −0.06); furthermore, neither intervention was found to be effective for this parameter. Conclusion: We concluded that subliminal priming with conscious reward stimuli results in improvements in immediate-term forward reach ability, which is superior to that achieved by subliminal priming with subconscious reward stimuli.